House rental advertisement via SMS functionality / Isma Aidil Hazari - Hazari, Isma Aidil (2009)
A House Rental Advertisement service is getting popular these days as evident by the number of house rental web sites that have gone online in the cyberspace. As UiTM increase its students' enrollment, the number of students seeking for accomodations is also increase especially off campus because residential colleges can only housed a certain number of students. UiTM's Non Resident Management Unit has been set up to assists students in looking for suitable house. However, the unit is still using manual process and paper based forms in capturing information, which is inefficient and time consuming. This study provided a convenient platform for developing the House Rental Advertisement System which integrates SMS technology with the website application for better management of the house rental data. House owners and students are able to share updated house rental information by simply send SMS. The development of website for house rental system provides interactive notification message to house owner so admin can manage the data efficiently and systematically. System Development Lify Cycle (SDLC) which is iterative development had been adopted. As a result, management of house rental data is being control efficiently. Future work for this system is expanding the scope not only to Shah Alam area but also to include all UiTM branches.